Regulating Illicit Enrichment into Indonesia’s Anti-Corruption Legal Reform Regime: Mengatur Pengayaan Tidak Sah ke dalam Reformasi Rezim Hukum AntiKorupsi Indonesia - Widiartana, Gregorius (Talenta Publisher, 2025)
The concept of illicit enrichment refers to a significant increase in a public official’s assets that cannot be reasonably explained in relation to their lawful income. As a legal instrument, illicit enrichment has been adopted in various jurisdictions to complement traditional anti-corruption measures, especially when proving the predicate offenses is difficult due to the sophisticated methods used to conceal corrupt practices. In Indonesia, despite the country’s commitment to combat corruption, the legal framework has yet to formally accommodate the concept of illicit enrichment as a standalone offense. This paper explores the potential of incorporating illicit enrichment into Indonesia’s anti-corruption regime by examining international practices, legal principles, and potential human rights concerns, particularly the presumption of innocence and the burden of proof. The analysis indicates that with proper safeguards, illicit enrichment provisions can be aligned with due process and serve as an effective tool in curbing unexplained wealth accumulation among public officials. The study also highlights the challenges Indonesia may face, including legislative reform, institutional readiness, and the need for public acceptance. Nevertheless, the integration of illicit enrichment into national law is not only a legal necessity but also a moral imperative in strengthening public accountability and restoring public trust. This paper concludes that a balanced and rights-respecting approach to illicit enrichment could significantly enhance the effectiveness of Indonesia’s anti-corruption framework.